Voltammetric sensor based on cobalt-poly(methionine)-modified glassy carbon electrode for determination of estriol hormone in pharmaceuticals and urine - Eliziana S. Gomes; Fernando R.F. Leite; Bruno R.L. Ferraz; Henrique A.J.L. Mourão; Andréa R. Malagutti (Elsevier, 2019)
A voltammetric sensor based on the electropolymerization of cobalt-poly(methionine) (Co-poly(Met)) on a glassy carbon electrode (GCE) was developed and applied for the determination of estriol by differential pulse voltammetry (DPV) for the first time. The electrochemical properties of the Co-poly(Met)/GCE were analysed by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). Scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) were used to characterize the polymers on the GCE surface. The deposition of the Co-poly(Met) film on the GCE surface enhanced the sensor electronic transfer. CV studies revealed that estriol exhibits an irreversible oxidation peak at +0.58 V for the Co-poly(Met)/GCE (vs. Ag/AgCl reference electrode) in 0.10 mol/L Britton-Robinson buffer solution (pH = 7.0). Different voltammetric scan rates (10-200 mV/s) suggested that the estriol oxidation on the Co-poly(Met)/GCE surface is controlled by adsorption and diffusion processes. Based on the optimized DPV conditions, the linear responses for estriol quantification were from 0.596 μmol/L to 4.76 μmol/L (R2 = 0.996) and from 5.66 μmol/L to 9.90 μmol/L (R2 = 0.994) with a limit of detection (LOD) of 0.0340 μmol/L and a limit of quantification (LOQ) of 0.113 μmol/L. The DPV-Co-poly(Met)/GCE method provided good intra-day and inter-day repeatability with RSD values lower than 5%. Also, no interference of real sample matrices was observed on the estriol voltammetric response, making the DPV-Co-poly(Met)/GCE highly selective for estriol. The accuracy test showed that the estriol recovery was in the ranges 96.7%-103% and 98.7%-102% for pharmaceutical tablets and human urine, respectively. The estriol quantification in pharmaceutical tablets performed by the Co-poly(Met)/GCE-assisted DPV method was comparable to the official analytical protocols. Keywords: Estriol, Electroanalysis, Differential pulse voltammetry, Cobalt-poly(methionine) film-modified glassy carbon electrode